Makna Hidup Adalah Kristus Berdasarkan Filipi 1 : 21 Dan Implikasinya Bagi Orang Percaya - Sri Lina Betty Lamsihar Simorangkir; Yonatan Alex Arifianto (CARAKA: Jurnal Teologi Biblika dan Praktika, 2020)
AbstractThe meaning of life is an important element in mental health and the functions of human life. A person may experiences despair and lost the certainty of life when he does not have meaning, purpose and value of life. The meaning of Paul's life based on Philippians 1: 20-21 shows only to the person of Christ. Christ became the beginning of his life. The encounter that brought repentance and life under the guidance of the Holy Spirit became the basis of the meaning of Paul's life. With descriptive qualitative methods and analyzing the text of the verse, provide information on the purpose of writing and provide an understanding that Christ must be the center of the life of believers. Longing to glorify Christ, and prioritizing life for Christ, not feel ashamed to preach the gospel and realize that death in God is a profitable thing are the guidance in living a life focused on God.  AbstrakMakna hidup merupakan elemen penting dalam kesejahteraan atau kesehatan mental dan fungsi hidup manusia. Seseorang mengalami putus asa dan tidak memiliki kepastian hidup di saat tidak mempunyai makna, tujuan dan nilai hidup. Makna hidup Paulus berdasarkan Filipi 1:20-21 menunjukkan hanya kepada pribadi Kristus. Kristus menjadi awal dari kehidupannya  setelah  perjumpaan yang membawa pertobatan serta hidup dalam pimpinan Roh Kudus menjadi dasar dari makna hidup Paulus. Dengan metode kualitatif deskriptif dan menganalisa teks ayat tersebut, dapat memberikan informasi tujuan penulisan serta memberi pemahaman bahwa Kristus harus menjadi pusat kehidupan orang percaya. Kerinduan memuliakan Kristus, dan memprioritaskan hidup bagi Kristus, serta tidak merasa malu memberitakan Injil dan menyadari bahwa kematian dalam Tuhan adalah hal yang menguntungkan. Maka hal itu menjadi pegangan dalam menjalani hidup fokus kepada Tuhan.